LOSS of EXPONENTIAL STABILITY FOR A THERMOELASTIC SYSTEM WITH MEMORY - Alves, Bruno Ferreira; Bastos, Waldemar Donizete [UNESP]; Raposo, Carlos Alberto (Texas State Univ, 2010)
In this article we study a thermoelastic system considering the linearized model proposed by Gurtin and Pipkin [8] instead of the Fourier's law for the heat flux. We use theory of semigroups [9, 11] combining Pruss' Theorem [10] and the idea developed in [5] to show that the system is not exponentially stable.
Keywords: Heat conduction with memory; C-0-semigroup; decay of solutions; thermoelastic system